0479 Novel Flow Limitation/Obstruction With Recovery Breath (FLOW) Event Identifies Obstructive Burden In Mild Obstructive Sleep Apnea. (27th April 2018) - Johnson, K G; Johnson, D C; Visintainer, P F; Kryger, M H; Thomas, R J; Linderauer, P; Feldmann, E
Abstract: Introduction: Traditional apnea-hypopnea measures, especially with home sleep apnea testing (HSAT) without arousal data are inadequate for representing clinically significant events in mild obstructive sleep apnea (OSA). Optimizing assessment of obstructive burden may improve the identification of patients at risk for adverse outcomes from OSA. We previously defined a novel event, F low L imitation/O bstruction W ith recovery (FLOW). Our aim is to show that FLOW scores most respiratory-related arousals (RRA) including hypopnea with arousals (HA) and respiratory-effort-related arousals (RERAs) and also captures obstructive events missed by traditional scoring. Methods: Mild OSA was defined as CPAP-treated patients with AHI using hypopneas with ≥4% desaturations <15. Twenty full-night polysomnography studies in mild OSA patients (10 women) were rescored for traditional obstructive events, FLOW events and non-respiratory event related arousals (NRA). Apnea-hypopnea indexes using hypopneas with ≥4% desaturations (AHI4), hypopneas with ≥3% desaturations (AHI3), hypopneas with ≥3% or arousals (AHI3A) were determined. We determined how often FLOW events were scored at the same time as RRA events and NRA or were not associated with any traditionally scored event. Results: The average AHI4, AHI3, and AHI3A were 2.6 ± 2.7, 5.2 ± 4.1, and 13.3 ± 7.0 events per hour respectively. The average AHI4/FLOW and AHI3/FLOW indexes are 26.3 ± 10.5 and 28.9 ± 11.8. 2495 FLOW events were present in 20 patients. FLOW was concurrent with 1060 (80%) of all RRA events (79% of both HA and RERA) and 41 (8%) of NRA. 1394 FLOW events (53%) were not associated with any traditional event or arousal. There were no significant gender differences in FLOW events. Conclusion: FLOW scores a high proportion of HA and RERA that are unscorable with HSAT. While >50% of FLOW events are not associated with traditional events, the low concurrence of FLOW with NRA suggests that FLOW is accurately representing airflow disruptions due to OSA. AHI/FLOW combination may help stratify the severity of disease and prediction of which mild patients will benefit from treatment. Clinical significance of AHI/FLOW needs to be evaluated in future studies. Support (If Any): Baystate Health Research Pilot Award.